2016
DOI: 10.1111/hel.12296
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin Containing Triple Therapy and Rifabutin with Bismuth Containing Quadruple Therapy for Third‐Line Treatment of Helicobacter pylori Infection: Two Pilot Studies

Abstract: The addition of bismuth subcitrate to a triple therapy that includes proton pump inhibitors, amoxicillin, and rifabutin in patients who are treated for the third time for H. pylori infection resulted in a 30% therapeutic gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 53 publications
2
32
0
1
Order By: Relevance
“…This was a prospective single‐center, randomized, open‐label trial conducted as two pilot studies in adult patients with H pylori infection as described previously …”
Section: Methodsmentioning
confidence: 99%
“…This was a prospective single‐center, randomized, open‐label trial conducted as two pilot studies in adult patients with H pylori infection as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Recently, two pilot non-randomized studies evaluated 10 day twice a day rifabutin triple therapy and separately a 10 day rifabutin quadruple therapy in which bismuth subcitrate was added twice a day. In this quadruple therapy, the cure rate without the addition of bismuth was poor (66.7%) but increased to 96.6% (28/29) with the addition of bismuth [56]. At this time one can only conclude that the details for producing a reliable rifabutin-containing therapy are still unknown.…”
Section: Rifabutin-containing Regimensmentioning
confidence: 99%
“…A study from Japan found in third‐ or fourth‐line therapy that 83.3% achieved eradication after 10 days of rifabutin‐based triple therapy and 94.1% after 14 days . A separate pilot study from Italy reported 96.6% for a 10‐day bismuth‐based quadruple regimen containing rifabutin compared to 66.7 in the 10‐day rifabutin‐based triple therapy arm . Less impressive results were found in a 12‐patient cohort in Korea in whom only 50% achieved eradication although this study was significantly skewed by the fact that some patients received therapy for 7 days and others 14 days .…”
Section: Rifabutinmentioning
confidence: 70%